Anti-angiogenic and Antioxidant Activities of Capparis spinosa L. in Rat Aortic Ring and CAM Models - Abbas, Atyaf; majed, Hebah; alrajhi, Shaymaa H. (Journal of Pharmacology and Drug Development, 2026)
Objective: Angiogenesis is the formation of new blood vessels from pre-existing vasculature, a basic and tightly controlled biological process. Angiogenesis is essential for tissue regeneration, wound healing, and embryonic development under normal physiological conditions. However, under pathological conditions, dysregulated angiogenesis contributes to several diseases, including cancer, making it an important therapeutic target. Accordingly, natural products, including Capparis spinosa L. have attracted considerable attention as promising anti-angiogenic agents. C. spinosa is rich in bioactive phytochemicals such as flavonoids and phenolic compounds that have been reported to possess anti-angiogenic potential. This study aimed to evaluate the anti-angiogenic and antioxidant activities of Capparis spinosa leaf extracts using complementary ex vivo and in vivo models. Methods: The rat aortic ring anti-angiogenesis assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, and chick chorioallantoic membrane (CAM) assay were carried out in the tissue culture laboratory of the Department of Pharmacology, College of Pharmacy, Al-Nahrain University. Results: The ethanolic extract demonstrated significant inhibition of microvessel outgrowth in the rat aortic ring assay, with an IC₅₀ value of 16.2 µg/mL and reduced neovascularisation in the CAM model, with an inhibition zone of 12±1.83 mm. The extract also exhibited concentration-dependent antioxidant activity in the DPPH assay. Conclusions: The ethanolic extract of Capparis spinosa L. exhibits significant anti-angiogenic and antioxidant activities and represents a promising natural source of compounds capable of modulating angiogenesis and oxidative stress, supporting its potential therapeutic applications.